Kyrgyz Republic - Livestock Sector Review : Embracing the New Challenges - World Bank (Washington, DC, 2012)
Continuing a long Kyrgyz tradition, the livestock sector is one of the strongest components of the rural economy. The sector contributes substantially to the national economy by providing high value food, income, employment and foreign exchange. There are also significant indirect benefits which include reduced risks to human health, more sustainable use of arable land and pastures, access to lucrative markets and the possibility to add value to livestock products. The processing and marketing of livestock products are also attractive to women. Available evidence suggests that recent growth in the value of sector output was due mostly to a strong increase in producer prices and only a small increase in productivity - despite the ample scope for growth of the latter. Productivity levels are low - number of calves/lambs born per 100 cows/ewes, milk yields, wool output and animal growth rates fall well short of genetic potential of the current mix of animal breeds and international industry standards. Current levels of animal productivity are low - due to poor nutrition, the high incidence of diseases, heavy affliction with parasites, and poor animal and farm management.